Cloning, Expression, Pharmacological Characterization and Anatomical Distribution of Melanocortin Receptors in an Evolutionary Perspective - Ringholm, Aneta I. (Uppsala universitet, Institutionen för neurovetenskap, 2004)
The melanocortin (MC) receptors are G-protein coupled receptors thatparticipate in several important physiological functions such as the regulation of the energy balance. This thesis focuses on the evolutionary aspect of the MC receptors and their pharmacology. One MC4 receptor and two MC5 receptor subtypes were found in a teleost fish, zebrafish. This indicates that the MC receptor subtypes arose very early in vertebrate evolution. Important pharmacological and functional properties, as well as gene structure and syntenic relationships have been highly conserved over a period of more than 400 million years implying that these receptors participate in vital physiological functions. Moreover, we found a MC4 receptor from a shark, spiny dogfish that represents the most distant MC receptor gene cloned to date. We also characterized the pharmacology of a MC4 receptor in goldfish. The conserved central expression pattern and physiological role in regulation of food intake of the MC4 receptor suggests that neuronal pathways of the melanocortin system may be important for regulation of energy homeostasis in most vertebrates. We determined the chromosomal position of the chicken MC receptors genes and found conserved synteny of the MC2, MC5, and MC4 receptor genes. These results suggest that there exist a clustering of these genes that is ancient. Analysis of conserved synteny with mammalian genomes and paralogon segments prompted us to predict an ancestral gene organization that may explain how this family has been formed through both local duplication and tetraploidization processes. There are several common point mutations in the human MC1 receptor that are over represented in North European red-heads, and in individuals with pale skin. We pharmacologically characterised four naturally occurring human MC1 receptor variants providing molecular explanation to the respective phenotype. The MC receptor subtypes have highly diverse physiological functions despite having relative high similarities in their primary structure. Our studies on the structural and functional properties of the MC receptor subtypes have provided insight into the molecular mechanism of how the specification of these receptors may have occurred.